Ceramics, methods of making and uses thereof

CN119038988BActive Publication Date: 2026-10-16SHANGHAI TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411163964.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2026-10-16
Estimated Expiration
2044-08-23

AI Technical Summary

Technical Problem

但典型的织构陶瓷材料制备技术(模板法、热加工和磁场定向法等)仍只是集中在传统陶瓷材料,开发可应用于电池,尤其是锂离子电池领域的织构陶瓷仍鲜有报道,有待进一步发展

Benefits of technology

[0012] This invention provides a ceramic, particularly a large-grain ceramic, which can be used as a fuel cell electrolyte or a textured lithium-conducting material. Specifically, the ceramic of this invention employs a gas-solid reaction sintering method, utilizing a gaseous compound to react with a porous electrolyte or electrode precursor preform. Under the induction of a concentration gradient, a textured lithium-conducting material with large grains and a fuel cell electrolyte are successfully prepared. The textured lithium-conducting material with large grains includes a solid electrolyte with large columnar crystals (e.g., lithium lanthanum zirconium oxide, Li7La3Zr2O). 12 The lithium-conducting materials (such as lithium cobalt oxide, LiCoO2, LCO; lithium manganese oxide, Li2MnO3, LMO, etc.) and electrode materials also exhibit internal grain alignment along the ion transport direction and/or crystallographic orientation in that direction. The fuel cell electrolyte is a large-grained, high-density ceramic electrolyte (e.g., La2Zr2O7 ceramic electrolyte). In summary, whether it's a textured lithium-conducting material or a fuel cell electrolyte, the significantly increased grain size, regular grain arrangement, or crystallographic orientation greatly reduces the probability of ions crossing grain boundaries with poor ion transport performance, while also avoiding tortuous transport paths, thus constructing a faster and more efficient ion pathway.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119038988B_ABST
    Figure CN119038988B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of ceramics, in particular to a kind of ceramic, preparation method and its application, especially in the application of battery field.The ceramic is lithium-conducting material or fuel cell electrolyte with texture characteristics, and the lithium-conducting material with texture characteristics is selected from solid electrolyte with texture characteristics or electrode material with texture characteristics.The present application uses the method of gas-solid reaction sintering, utilizes gaseous compound and porous electrolyte or electrode precursor blank body reaction, under the induction of concentration gradient, successfully prepares lithium-conducting material with texture characteristics and fuel cell electrolyte with large size grain.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ceramic technology, and in particular to a ceramic, its preparation method, and its application, especially in the field of batteries. Background Technology

[0002] Polycrystalline electrolytes or electrode materials are generally composed of grains and grain boundaries. Since the structure and composition of grain boundaries differ from those of the bulk grains, their ion transport also differs. Numerous studies have shown that grain boundaries in inorganic solid electrolytes increase ion migration resistance, exhibit lower conductivity than grain conductivity, and possess higher diffusion activation energies than grains, thus reducing the overall ionic conductivity of the electrolyte. Therefore, optimizing synthesis conditions to increase the grain size of solid electrolytes, improve grain boundary contact, and reduce the proportion of grain boundaries can effectively improve both grain boundary conductivity and overall conductivity.

[0003] One of the most common methods is to add sintering aids during electrolyte sintering. Sintering aids can promote grain growth, reduce grain boundary volume, and thus lower grain boundary resistance. In the traditional solid electrolyte preparation process, sintering aids are mainly mixed thoroughly with electrolyte powder in the form of solid powder, then the mixed powder is pressed into a green body, and then sintered by heating. This method makes it difficult to thoroughly mix the powder and sintering aids, and the sintering temperature is relatively high. Another more effective method to improve ionic conductivity is to construct materials with textured properties. As an inorganic non-metallic material with crystallographic orientation or regular grain arrangement, textured ceramics exhibit significant anisotropy in properties (such as thermoelectricity, piezoelectricity, ferroelectricity, and conductivity) compared to traditional isotropic ceramics. Designing textured materials that are more conducive to ion conduction can greatly reduce the tortuosity of ion transport paths and significantly improve the ion transport performance of the material. However, typical textural ceramic material preparation techniques (template method, thermal processing and magnetic field orientation method, etc.) are still concentrated on traditional ceramic materials. There are few reports on the development of textural ceramics that can be applied to batteries, especially lithium-ion batteries, and further development is needed. Summary of the Invention

[0004] In view of the shortcomings of the prior art described above, the purpose of this invention is to provide a ceramic, especially a large-grain ceramic, which can be used as a fuel cell electrolyte or a lithium-conducting material with textured characteristics to solve the problems in the prior art.

[0005] To achieve the above and other related objectives, the present invention provides a ceramic, which is a lithium-conducting material with textured characteristics or a fuel cell electrolyte, wherein the lithium-conducting material with textured characteristics is selected from solid electrolytes with textured characteristics or electrode materials with textured characteristics.

[0006] Another aspect of the present invention provides a method for preparing the ceramic, the method comprising the following steps:

[0007] 1) The precursor powder and polymer solution are ground and mixed, and then pressed into precursor powder cakes;

[0008] 2) The precursor powder obtained in step 1) is subjected to high-temperature degumming to obtain a porous powder.

[0009] 3) Place the porous powder cake obtained in step 2) in a crucible covered with oxide, wherein the porous powder cake is placed directly above the oxide and the porous powder cake is not in direct contact with the oxide; heat and cool to room temperature in a sealed environment to obtain the final product.

[0010] The present invention also provides the application of the aforementioned ceramics and / or ceramics prepared by the aforementioned methods in the field of batteries.

[0011] Compared with the prior art, the beneficial effects achieved by the present invention are as follows:

[0012] This invention provides a ceramic, particularly a large-grain ceramic, which can be used as a fuel cell electrolyte or a textured lithium-conducting material. Specifically, the ceramic of this invention employs a gas-solid reaction sintering method, utilizing a gaseous compound to react with a porous electrolyte or electrode precursor preform. Under the induction of a concentration gradient, a textured lithium-conducting material with large grains and a fuel cell electrolyte are successfully prepared. The textured lithium-conducting material with large grains includes a solid electrolyte with large columnar crystals (e.g., lithium lanthanum zirconium oxide, Li7La3Zr2O). 12 The lithium-conducting materials (such as lithium cobalt oxide, LiCoO2, LCO; lithium manganese oxide, Li2MnO3, LMO, etc.) and electrode materials also exhibit internal grain alignment along the ion transport direction and / or crystallographic orientation in that direction. The fuel cell electrolyte is a large-grained, high-density ceramic electrolyte (e.g., La2Zr2O7 ceramic electrolyte). In summary, whether it's a textured lithium-conducting material or a fuel cell electrolyte, the significantly increased grain size, regular grain arrangement, or crystallographic orientation greatly reduces the probability of ions crossing grain boundaries with poor ion transport performance, while also avoiding tortuous transport paths, thus constructing a faster and more efficient ion pathway. Attached Figure Description

[0013] Figure 1 The diagram shows a process flow chart for preparing columnar textured ceramics by gas-solid reaction sintering (using lithium lanthanum zirconium oxide as an example).

[0014] Figure 2 The images show the structural and morphological characterization of the textured ceramic electrolyte (lithium lanthanum zirconium oxide) and electrode materials (lithium cobalt oxide, lithium manganese oxide) in Examples 1-3.

[0015] Figure 3 The image shows the morphology and elemental distribution of a single lithium lanthanum zirconium oxide columnar crystal in Example 1.

[0016] Figure 4 The image shows the transmission electron microscopy characterization of the columnar textured ceramic electrolyte (lithium lanthanum zirconium oxide) and electrode materials (lithium manganese oxide, lithium cobalt oxide) in Examples 1-3.

[0017] Figure 5 The image shows a comparison of the electrochemical performance of the large-sized columnar crystal lithium lanthanum zirconium oxygen electrolyte in Example 1 and the small-sized equiaxed crystal lithium lanthanum zirconium oxygen electrolyte in Comparative Example 1.

[0018] Figure 6 The image shows a comparison of the electrochemical performance of the large-size columnar crystal lithium cobalt oxide electrode in Example 2 and the small-size equiaxed crystal lithium cobalt oxide electrode in Comparative Example 2.

[0019] Figure 7 The image shows the XRD characterization of the lanthanum zirconate electrolyte sheet after gas-solid sintering in Example 4.

[0020] Figure 8 The image shows the density and SEM images of lanthanum zirconate electrolyte sheets after gas-solid sintering at different temperatures with the same amount of zinc oxide.

[0021] Figure 9 The image shows the density and SEM images of lanthanum zirconate electrolyte sheets after gas-solid sintering at 1400℃ with different amounts of zinc oxide.

[0022] Figure 10 The image shown is a cross-sectional SEM image of the lanthanum zirconate electrolyte obtained by sintering using the conventional solid-state mixing method in Comparative Example 3.

[0023] Figure 11 The comparison shows the ionic conductivity and activation energy of the lanthanum zirconate electrolyte obtained by gas-solid sintering in Example 4 and the lanthanum zirconate electrolyte obtained by sintering after conventional solid-phase mixing in Comparative Example 3.

[0024] Figure 12 The image shown is a SEM image of a lanthanum zirconate electrolyte sheet after gas-solid sintering at 1400℃ for 10 h with 20wt% zinc oxide. Detailed Implementation

[0025] The following details a specific embodiment of a ceramic, its preparation method, and its application.

[0026] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0027] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0028] Through extensive experimental research, the applicant has developed a ceramic, particularly a large-grained ceramic, which can be used as a fuel cell electrolyte or a textured lithium-conducting material. Specifically, the ceramic of this invention employs a gas-solid reaction sintering method, utilizing a gaseous compound to react with a porous electrolyte or electrode precursor preform. Under the induction of a concentration gradient, a textured lithium-conducting material with large grains and a fuel cell electrolyte were successfully prepared. The textured lithium-conducting material with large grains includes a solid electrolyte with large columnar crystals (e.g., lithium lanthanum zirconium oxide, Li7La3Zr2O). 12 The lithium-conducting materials (such as lithium cobalt oxide, LiCoO2, LCO; lithium manganese oxide, Li2MnO3, LMO, etc.) and electrode materials have internal grains that are aligned along the ion transport direction or have crystallographic orientation in that direction. The fuel cell electrolyte is a large-grained, high-density ceramic electrolyte (e.g., La2Zr2O7 ceramic electrolyte). In summary, whether it is a lithium-conducting material with textured features or a fuel cell electrolyte, the significant increase in grain size, the regular arrangement of columnar grains, or crystallographic orientation greatly reduces the probability of ions crossing grain boundaries with poor ion transport performance, and also avoids tortuous transport paths, thus constructing a faster and more efficient ion pathway. Based on this, the present invention was completed.

[0029]

ceramics

[0030] The present invention provides a ceramic, wherein the ceramic is a lithium-conducting material with textured features or a fuel cell electrolyte, and the lithium-conducting material with textured features is selected from solid electrolytes with textured features or electrode materials with textured features.

[0031] <Lithium-conducting materials with texture characteristics>

[0032] The textured lithium-conducting material is columnar crystal, with a grain size of 50–200 μm in length and 10–50 μm in diameter. Optionally, the grain size of the textured lithium-conducting material is 50–150 μm or 150–200 μm in length, and 10–30 μm or 30–50 μm in diameter.

[0033] The solid electrolyte with textured characteristics in the ceramic provided by this invention is lithium lanthanum zirconium oxide (Li7La3Zr2O). 12 Optionally, the lithium lanthanum zirconium oxide crystals have a length of 50–200 μm and a diameter of 10–50 μm, with no obvious crystallographic orientation, and the columnar crystals are arranged perpendicular to the electrolyte surface. More preferably, the lithium lanthanum zirconium oxide crystals have a length of 50–150 μm or 150–200 μm, and their diameter can be selected as 10–30 μm or 30–50 μm.

[0034] In the ceramic provided by the present invention, the electrode material with texture features may optionally be selected from one or both of lithium cobalt oxide (LiCoO2) and lithium manganese oxide (Li2MnO3).

[0035] Further optionally, the lithium cobalt oxide has a grain size of 100-150 μm in length and 30-50 μm in diameter, exhibiting a crystallographic orientation with columnar crystals arranged perpendicular to the electrode surface, and its (100) crystal plane perpendicular to the surface. The grain size of lithium cobalt oxide can, for example, be 100-120 μm or 120-150 μm in length, and the diameter can, for example, be 30-40 μm or 40-50 μm.

[0036] Further optionally, the lithium manganese oxide has a grain size of 50-80 μm in length and 20-40 μm in diameter, with a crystallographic orientation, columnar crystals arranged perpendicular to the electrode surface, and its (100) crystal plane perpendicular to the surface. The grain size of lithium manganese oxide can be, for example, 50-60 μm, 60-70 μm, or 70-80 μm in length, and its diameter can be selected as 20-30 μm or 30-40 μm.

[0037] <Fuel Cell Electrolyte>

[0038] The fuel cell electrolyte is a La2Zr2O7 ceramic electrolyte with an average grain diameter of 20-30 μm and a density greater than 95%. Optionally, the average grain diameter can be, for example, 20-25 μm or 25-30 μm.

[0039] Methods for preparing ceramics

[0040] The present invention also provides a method for preparing ceramics, the method comprising the following steps:

[0041] 1) The precursor powder and polymer solution are ground and mixed, and then pressed into precursor powder cakes;

[0042] 2) The precursor powder obtained in step 1) is subjected to high-temperature degumming to obtain a porous powder.

[0043] 3) Place the porous powder cake obtained in step 2) in a crucible covered with oxide, wherein the porous powder cake is placed directly above the oxide and the porous powder cake is not in direct contact with the oxide; heat and cool to room temperature in a sealed environment to obtain the final product.

[0044] In the ceramic preparation method provided by this invention, step 1) involves grinding and mixing the precursor powder with a polymer solution, and then pressing it into a precursor powder cake. Specifically:

[0045] In step 1) of this invention, the mass ratio of the precursor powder to the polymer solution is (85-95):(5-15). It can be selected as (80-85):(15-20); (85-90):(10-15); or (90-95):(5-10).

[0046] In step 1) of this invention, the precursor powder is selected from electrolyte precursor powder, electrode precursor powder or other precursor powder.

[0047] Optionally, the electrolyte precursor powder is lanthanum zirconate powder.

[0048] Optionally, the electrode precursor powder is one or more of cobalt tetroxide powder and manganese tetroxide powder.

[0049] In step 1) of this invention, the polymer solution is selected from polyvinyl alcohol (PVA) solution. For example, it can be an aqueous solution of polyvinyl alcohol with a concentration of 5 wt% to 15 wt%, optionally 5 wt% to 10 wt% or 10 wt% to 15 wt%. Preferably, it is 10 wt%.

[0050] In step 1) of this invention, the pressing pressure is 100-400 MPa. It can be selected as 100-200 MPa, 200-300 MPa, or 300-400 MPa, etc.

[0051] In step 1) of this invention, the pressing time is 1 to 5 minutes. It can be selected as 1 to 3 minutes or 3 to 5 minutes, etc.

[0052] In step 1) of this invention, the thickness of the precursor powder is 150–800 μm. It can be selected as 150–200 μm, 200–800 μm, 150–300 μm, 300–600 μm, or 600–800 μm, etc.

[0053] In the ceramic preparation method provided by this invention, step 2) involves calcining the precursor powder cake obtained in step 1) at high temperature to obtain a porous powder cake. Specifically:

[0054] In step 2) of this invention, the temperature for high-temperature debinding is 700–1200°C. It can be selected as 700–800°C, 800–1050°C, 1050–1200°C, 1050–1100°C, 1100–1200°C, 1050–1100°C, 1100–1200°C, 1100–1150°C, or 1150–1200°C, etc. The high-temperature sintering can be carried out in a muffle furnace.

[0055] In step 2) of this invention, the high-temperature degumming time is 1 hour to 3 hours, which can be 1 hour to 2 hours or 2 hours to 3 hours, etc. Preferably, it is 2 hours.

[0056] In step 2) of this invention, the porous powder cake has a porous structure with a density of 75% to 80%. Excessive density hinders the diffusion of gaseous lithium oxide, while excessive looseness hinders sintering between grains. Optionally, the density can be, for example, 75% to 78% or 78% to 80%.

[0057] In the ceramic preparation method provided by this invention, step 3) involves placing the porous powder cake obtained in step 2) in a crucible covered with oxide, wherein the porous powder cake is placed directly above the oxide and the porous powder cake does not directly contact the oxide; the ceramic is then heated and cooled to room temperature in a sealed environment to obtain the final product. Specifically:

[0058] In step 3) of this invention, the oxide is selected from lithium oxide or zinc oxide.

[0059] In step 3) of this invention, the crucible is a magnesium oxide crucible.

[0060] In step 3) of this invention, the heating temperature is 1050–1800℃, and the heating time is 2–20 hours. Heating can be carried out in a muffle furnace. Optionally, the heating temperature is 1050–1250℃, 1250–1400℃, 1250–1300℃, 1300–1400℃, 1300–1350℃, 1350–1400℃, 1400–1600℃, or 1600–1800℃.

[0061] <Preparation method of lithium-conducting materials with texture characteristics>

[0062] The preparation method of lithium-conducting materials with textured characteristics includes the following steps:

[0063] 1) The precursor powder and polymer solution are ground and mixed, and then pressed into precursor powder cakes;

[0064] 2) The precursor powder obtained in step 1) is subjected to high-temperature degumming to obtain a porous powder.

[0065] 3) Place the porous powder cake obtained in step 2) in a crucible covered with oxide, wherein the porous powder cake is placed directly above the oxide and the porous powder cake is not in direct contact with the oxide; heat and cool to room temperature in a sealed environment to obtain the final product.

[0066] In the method for preparing lithium-conducting materials with textured characteristics provided by this invention, step 1) involves grinding and mixing the precursor powder with a polymer solution, and then pressing it into a precursor powder cake. Specifically:

[0067] In step 1) of this invention, the mass ratio of the precursor powder to the polymer solution is (85-95):(5-15). It can be selected as (80-85):(15-20); (85-90):(10-15); or (90-95):(5-10).

[0068] In step 1) of this invention, the precursor powder is selected from electrolyte precursor powder, electrode precursor powder or other precursor powder.

[0069] Optionally, the electrolyte precursor powder is lanthanum zirconate powder.

[0070] Optionally, the electrode precursor powder is one or more of cobalt tetroxide powder and manganese tetroxide powder.

[0071] In step 1) of this invention, the polymer solution is selected from polyvinyl alcohol (PVA) solution. For example, it can be an aqueous solution of polyvinyl alcohol with a concentration of 5 wt% to 15 wt%, optionally 5 wt% to 10 wt% or 10 wt% to 15 wt%. Preferably, it is 10 wt%.

[0072] In step 1) of this invention, the pressing pressure is 100-400 MPa. It can be selected as 100-200 MPa, 200-300 MPa, or 300-400 MPa, etc.

[0073] In step 1) of this invention, the pressing time is 1 to 5 minutes. It can be selected as 1 to 3 minutes or 3 to 5 minutes, etc.

[0074] In step 1) of this invention, the thickness of the precursor powder is 150–800 μm. It can be selected as 150–200 μm, 200–800 μm, 150–300 μm, 300–600 μm, or 600–800 μm, etc.

[0075] In the method for preparing lithium-conducting materials with textured characteristics provided by this invention, step 2) involves calcining the precursor powder cake obtained in step 1) at high temperature to obtain a porous powder cake. Specifically:

[0076] In step 2) of this invention, the temperature for high-temperature debinding is 700–1200°C. It can be selected as 700–800°C, 800–1050°C, 1050–1200°C, 1050–1100°C, 1100–1200°C, 1050–1100°C, 1100–1200°C, 1100–1150°C, or 1150–1200°C, etc. The high-temperature sintering can be carried out in a muffle furnace.

[0077] In step 2) of this invention, the high-temperature degumming time is 1 hour to 3 hours, which can be 1 hour to 2 hours or 2 hours to 3 hours, etc. Preferably, it is 2 hours.

[0078] In step 2) of this invention, the porous powder cake has a porous structure with a density of 75% to 80%. Excessive density hinders the diffusion of gaseous lithium oxide, while excessive looseness hinders sintering between grains. Optionally, the density can be, for example, 75% to 78% or 78% to 80%.

[0079] In the method for preparing the textured lithium-conducting material provided by this invention, step 3) involves placing the porous powder cake obtained in step 2) in a crucible covered with oxide, wherein the porous powder cake is placed directly above the oxide and the porous powder cake does not directly contact the oxide; the material is then heated and cooled to room temperature in a sealed environment to obtain the final product. Specifically:

[0080] In step 3) of this invention, the oxide is selected from lithium oxide. The lithium oxide is 20 wt% to 50 wt% of the porous powder cake by mass. It can be selected as 20 wt% to 30 wt% or 30 wt% to 50 wt%.

[0081] In step 3) of this invention, the crucible is a magnesium oxide crucible.

[0082] In step 3) of this invention, the heating temperature is 1050–1200℃, and the heating time is 2–20 hours. Heating can be carried out in a muffle furnace. Specifically: the reaction temperature for lithium lanthanum zirconium oxide is 1250℃, and the reaction time is 2-15 hours; the temperature for lithium cobalt oxide and lithium manganese oxide electrode materials is 1050℃, and the reaction time is 5-15 hours. Heating can also be carried out in a muffle furnace.

[0083] At the above heating temperature, oxides such as lithium oxide can be vaporized to form gaseous compounds. The gaseous compounds react with porous precursor preforms to prepare solid electrolytes and electrode materials with textured characteristics of large-sized columnar crystals.

[0084] Preparation methods of fuel cell electrolytes

[0085] The present invention also provides a method for preparing a fuel cell electrolyte, the method comprising the following steps:

[0086] 1) The precursor powder and polymer solution are ground and mixed, and then pressed into precursor powder cakes;

[0087] 2) The precursor powder obtained in step 1) is subjected to high-temperature degumming to obtain a porous powder.

[0088] 3) Place the porous powder cake obtained in step 2) in a crucible covered with oxide, wherein the porous powder cake is placed directly above the oxide and the porous powder cake is not in direct contact with the oxide; heat and cool to room temperature in a sealed environment to obtain the final product.

[0089] In the method for preparing fuel cell electrolyte provided by this invention, step 1) involves grinding and mixing precursor powder with a polymer solution, and then pressing the mixture into a precursor powder cake. Specifically:

[0090] In step 1) of this invention, the mass ratio of the precursor powder to the polymer solution is (85-95):(5-15). It can be selected as (80-85):(15-20); (85-90):(10-15); or (90-95):(5-10).

[0091] In step 1) of this invention, the precursor powder is selected from electrolyte precursor powder, electrode precursor powder or other precursor powder.

[0092] Optionally, the electrolyte precursor powder is lanthanum zirconate powder.

[0093] Optionally, the electrode precursor powder is one or more of cobalt tetroxide powder and manganese tetroxide powder.

[0094] In step 1) of this invention, the polymer solution is selected from polyvinyl alcohol (PVA) solution. For example, it can be an aqueous solution of polyvinyl alcohol with a concentration of 5 wt% to 15 wt%, optionally 5 wt% to 10 wt% or 10 wt% to 15 wt%. Preferably, it is 10 wt%.

[0095] In step 1) of this invention, the pressing pressure is 100-400 MPa. It can be selected as 100-200 MPa, 200-300 MPa, or 300-400 MPa, etc.

[0096] In step 1) of this invention, the pressing time is 1 to 5 minutes. It can be selected as 1 to 3 minutes or 3 to 5 minutes, etc.

[0097] In step 1) of this invention, the thickness of the precursor powder is 150–800 μm. It can be selected as 150–200 μm, 200–800 μm, 150–300 μm, 300–600 μm, or 600–800 μm, etc.

[0098] In the method for preparing fuel cell electrolyte provided by this invention, step 2) involves calcining the precursor powder cake obtained in step 1) at high temperature to obtain a porous powder cake. Specifically:

[0099] In step 2) of this invention, the temperature for high-temperature debinding is 700–1200°C. It can be selected as 700–800°C, 800–1050°C, 1050–1200°C, 1050–1100°C, 1100–1200°C, 1050–1100°C, 1100–1200°C, 1100–1150°C, or 1150–1200°C, etc. The high-temperature sintering can be carried out in a muffle furnace.

[0100] In step 2) of this invention, the high-temperature degumming time is 1 hour to 3 hours, which can be 1 hour to 2 hours or 2 hours to 3 hours, etc. Preferably, it is 2 hours.

[0101] In step 2) of this invention, the porous powder cake has a porous structure with a density of 75% to 80%. Excessive density hinders the diffusion of gaseous lithium oxide, while excessive looseness hinders sintering between grains. Optionally, the density can be, for example, 75% to 78% or 78% to 80%.

[0102] In the method for preparing fuel cell electrolyte provided by this invention, step 3) involves placing the porous powder cake obtained in step 2) in a crucible covered with oxide, wherein the porous powder cake is placed directly above the oxide and the porous powder cake does not directly contact the oxide; the electrolyte is then heated and cooled to room temperature in a sealed environment to obtain the final product. Specifically:

[0103] In step 3) of this invention, the oxide is selected from zinc oxide. The zinc oxide is 15 wt% to 30 wt% of the porous powder cake by mass percentage. It can be selected as 15 wt% to 20 wt% or 20 wt% to 30 wt%.

[0104] In step 3) of this invention, the crucible is a magnesium oxide crucible.

[0105] In step 3) of this invention, the heating temperature is 1400–1800℃, and the heating time is 2–20 hours. Heating can be carried out in a muffle furnace. Optionally, the heating temperature is 1400–1600℃ or 1600–1800℃. Specifically, the reaction temperature for the solid-state sintered lanthanum zirconate ceramic sheet is 1300–1400℃, and the heating time is 5–20 hours. Heating can be carried out in a muffle furnace.

[0106] At the aforementioned heating temperature, oxides, such as zinc oxide, can vaporize to form gaseous compounds. These gaseous compounds enter the porous precursor preform to promote sintering, thus preparing a solid electrolyte material with large grain size and high density (99.4%). Zinc oxide serves as the sintering agent.

[0107] In traditional solid electrolyte preparation processes, sintering aids are mainly mixed thoroughly with electrolyte powder in solid powder form, then the mixed powder is pressed into a green body, and finally sintered by heating. This invention develops a method for preparing large-size grain ceramic electrolytes using gaseous sintering aids. The La2Zr2O7 ceramic electrolyte obtained by sintering in a gaseous ZnO atmosphere has a sintering temperature reduced to 1300℃, resulting in a significantly increased crystal size and density, thus optimizing ionic conductivity.

[0108]

application

[0109] This invention also provides the application of the aforementioned ceramics in the field of batteries. The batteries may be, for example, lithium-ion batteries or fuel cells.

[0110] The beneficial effects of the present invention will be further illustrated below with reference to the embodiments.

[0111] To make the inventive objectives, technical solutions, and beneficial effects of this invention clearer, the invention is further described in detail below with reference to embodiments. However, it should be understood that the embodiments of this invention are merely for illustrative purposes and not for limiting the invention, and the embodiments are not limited to those given in the specification. Unless otherwise specified, specific experimental or operational conditions in the embodiments were prepared under conventional conditions or according to the conditions recommended by the material supplier.

[0112] Furthermore, it should be understood that the existence of other method steps before or after the combined steps, or the insertion of other method steps between these explicitly mentioned steps, does not preclude the existence of other method steps before or after the combined steps, or the insertion of other method steps between these explicitly mentioned steps, unless otherwise stated. It should also be understood that the combined connection relationship between one or more devices / apparatus mentioned in this invention does not preclude the existence of other devices / apparatus before or after the combined devices / apparatus, or the insertion of other devices / apparatus between these explicitly mentioned devices / apparatus, unless otherwise stated. Moreover, unless otherwise stated, the numbering of each method step is merely a convenient tool for identifying each method step, and not for limiting the order of the method steps or limiting the scope of the invention. Changes or adjustments to their relative relationships, without substantially altering the technical content, should also be considered within the scope of the invention.

[0113] Unless otherwise specified, all reagents, materials and instruments used in the following embodiments are commercially available.

[0114] Example 1:

[0115] ZrO2 and La2O3 were mixed at a molar ratio of 2:1 and sintered at 1500℃ for 6 hours to obtain lanthanum zirconate powder.

[0116] Lanthanum zirconate ceramic powder was obtained by solid-state method. 0.9 g of lanthanum zirconate powder was ground and mixed with 0.1 g of PVA aqueous solution (concentration 10 wt%), poured into a mold, and pressed under a pressure of 100-400 MPa for 1-5 minutes to form an electrolyte precursor powder cake with a thickness of 800 μm. The cake was degummed at 1200℃ for 2 hours to obtain a porous powder cake with a density of 78%. The degummed powder cake was placed in a magnesium oxide crucible containing 30 wt% lithium oxide (the porous powder cake by weight), with the lanthanum zirconate powder cake positioned above the lithium oxide without direct contact. The mixture was heated to 1250℃ in a muffle furnace at a heating rate of 5℃ / min and held for 2-15 hours. After cooling to room temperature, a lithium lanthanum zirconium oxide electrolyte sheet was polished. After gold sputtering on both sides to form a blocked battery, its ionic conductivity was measured to be 2.76 × 10⁻⁶. -5 S cm -1 Compared to traditional LLZO ceramic electrolytes (6.51×10⁻⁶), -7 S cm -1 There has been a significant improvement.

[0117] Figure 1 This is a schematic diagram of the process for preparing columnar textured ceramics (lithium lanthanum zirconium oxide) by gas-solid reaction sintering. The structure and morphology of the obtained lithium lanthanum zirconium oxide electrolyte sheet are detailed in [link to diagram]. Figure 2 A, Figure 2 D(XRD) and Figure 2G(SEM). The grain size of lithium lanthanum zirconium oxide is 150 μm in length and 30 μm in diameter, with no obvious crystallographic orientation, and the grains are aligned along the length. Figure 3 This describes the morphological characterization and elemental distribution of a single lithium-lanthanum-zirconium-oxygen columnar crystal. For example... Figure 4 A-4C shows the transmission electron microscopy characterization of a columnar textured ceramic electrolyte (lithium lanthanum zirconium oxide).

[0118] Comparative Example 1

[0119] Small-sized equiaxed lithium lanthanum zirconium oxide electrolyte

[0120] The equiaxed crystalline lithium lanthanum zirconium oxide electrolyte was prepared using a conventional solid-state reaction method, with LiOH·H₂O, La₂O₃, and ZrO₂ as starting materials. A 20% excess of LiOH·H₂O was added to compensate for lithium loss during high-temperature calcination. The stoichiometric amounts of the above-mentioned reagents were mixed in isopropanol and ball-milled at 600 rpm for 6 hours. The resulting powder was then calcined at 950°C for 6 hours. 500 mg of the calcined powder was poured into a 12 mm diameter mold and pressed into ceramic sheets under 400 MPa pressure. These sheets were then sintered in a magnesium oxide crucible at 1250°C for 40 minutes to obtain the equiaxed crystalline lithium lanthanum zirconium oxide ceramic electrolyte.

[0121] Combining Example 1 and Comparative Example 1, Figure 5 A and 5B are the impedance spectra of columnar LLZO electrolyte and equiaxed LLZO electrolyte, respectively. Columnar LLZO has only one grain impedance arc, while equiaxed LLZO has grain impedance arcs in the high-frequency region and grain boundary impedance arcs in the mid-frequency region. This indicates that columnar LLZO electrolyte does not need to frequently cross grain boundaries during lithium-ion transport (which would lead to a decrease in its ionic conductivity). Therefore, the ionic conductivity of columnar LLZO electrolyte is more than forty times higher than that of equiaxed LLZO electrolyte. Figure 5 C is a Debye plot fitted using the Lorentz function. The columnar LLZO electrolyte has a shorter relaxation time, which means it has faster ion transport. Figure 5 D represents the ionic conductivity of columnar LLZO electrolyte and equiaxed LLZO electrolyte at different temperatures. The conductivity was fitted using the Arrhenius equation, which showed that the columnar LLZO electrolyte has a lower activation energy, which is more conducive to ion transport. Figure 5 E and 5F represent the cycling performance of the two under continuously increasing current. The columnar LLZO electrolyte exhibits a higher critical current density, indicating that it can accept a larger ion transport flux without short-circuiting.

[0122] Example 2:

[0123] 0.2 g of cobalt oxide powder was ground and mixed with 0.05 g of PVA aqueous solution (concentration 10 wt%), poured into a mold, and pressed under a pressure of 100-400 MPa for 1-5 minutes to form an electrode precursor powder cake with a thickness of 200 μm. The cake was degummed at 1000℃ for 3 hours to obtain a porous powder cake with a density of 80%. The degummed powder cake was placed in a magnesium oxide crucible containing lithium oxide, with the cobalt oxide powder cake placed above lithium oxide (30 wt% of the porous powder cake) without direct contact. The mixture was heated in a muffle furnace to 1050℃ at a heating rate of 5℃ / min and held for 8-10 hours. After cooling to room temperature, a lithium cobalt oxide electrode material with crystallographic orientation was obtained. Compared to traditional untextured lithium cobalt oxide, this material exhibits superior ion transport performance.

[0124] For details on the structure and morphology of the obtained lithium cobalt oxide electrode material, please refer to [link to relevant documentation]. Figure 2 B. Figure 2 E(XRD) and Figure 2 H(SEM). The lithium cobalt oxide grains are 150 μm long and 50 μm in diameter, with columnar crystals arranged perpendicular to the electrode surface, and their (100) crystal planes perpendicular to the surface. For example... Figure 4 G-4I shows the transmission electron microscopy characterization of columnar textured ceramic lithium cobalt oxide.

[0125] Comparative Example 2

[0126] The lithium cobalt oxide electrode material prepared in Example 2 was ground to a particle size of 5-15 μm, pressed into a lithium cobalt oxide powder cake under a uniaxial pressure of 100-400 MPa, and sintered at 900-1050 degrees Celsius for 3 hours to obtain the control sample lithium cobalt oxide electrode material.

[0127] Compared to Comparative Example 2, the textured lithium cobalt oxide (LCO) material in Example 2 exhibits significant advantages in electrochemical performance. For example... Figure 6 Example 2 not only has a high conductivity (2.84 × 10⁻⁶), but also... -4 S cm -1 Compared to 2.27 × 10 in Comparative Example 2 -5 S cm -1 Moreover, its activation energy is lower (0.22 eV compared to 0.28 eV in Comparative Example 2), which means that under the same conditions, the synthesized lithium cobalt oxide material with texture features has easier ion migration and exhibits superior electrochemical performance.

[0128] Example 3:

[0129] 0.1 g of manganese oxide powder was ground and mixed with 0.05 g of PVA aqueous solution (concentration 10 wt%), poured into a mold, and pressed under a pressure of 100-400 MPa for 1-5 minutes to form an electrode precursor powder cake with a thickness of 150 μm. The cake was degummed at 1100℃ for 3 hours to obtain a porous powder cake with a density of 80%. The degummed powder cake was placed in a magnesium oxide crucible containing lithium oxide, with the manganese oxide powder cake placed on top of lithium oxide (30 wt% of the porous powder cake) without direct contact with the lithium oxide powder. The mixture was heated in a muffle furnace to 1250℃ at a heating rate of 5℃ / min and held for 10-15 hours. This yielded a Li₂MnO₃ material with crystallographic orientation. Compared to traditional untextured lithium manganese oxide, this material exhibits superior ion transport performance.

[0130] For details on the structure and morphology of the obtained lithium manganese oxide electrode material, please refer to [link to relevant documentation]. Figure 2 C Figure 2 F(XRD) and Figure 2 I(SEM). The lithium manganese oxide grains are 80 μm long and 30 μm in diameter, with columnar crystals arranged perpendicular to the electrode surface, and their (100) crystal planes perpendicular to the surface. For example... Figure 4 D-4F shows the transmission electron microscopy characterization of lithium manganese oxide ceramic with columnar crystal texture.

[0131] Example 4:

[0132] ZrO2 and La2O3 were mixed at a molar ratio of 2:1 and sintered at 1500℃ for 6 hours to obtain lanthanum zirconate powder.

[0133] Lanthanum zirconate ceramic powder was obtained by solid-state method. 0.9 g of lanthanum zirconate powder was ground and mixed with 0.1 g of PVA aqueous solution (concentration 10 wt%), poured into a mold, and pressed under a pressure of 100-400 MPa for 1-5 minutes to form an electrolyte precursor powder cake with a thickness of 600 μm. The cake was degummed at 1200℃ for 2 hours to obtain a porous powder cake with a density of 78%. The degummed powder cake was placed in a magnesium oxide crucible containing 20 wt% zinc oxide (by weight of the porous powder cake), ensuring the lanthanum zirconate powder cake did not directly contact the zinc oxide powder. The mixture was heated to 1400℃ in a muffle furnace at a heating rate of 5℃ / min and held for 5 hours. After cooling to room temperature, the lanthanum zirconate electrolyte sheet was polished. Silver paste was evenly coated on both sides of the ceramic sheet as a blocking electrode, and an external silver wire was connected as a conductor to the electrochemical performance testing equipment. The electrolyte sample was sealed in a quartz glass tube, humidified air was introduced, and the sample was heated to test its ionic conductivity at different temperatures. Compared to lanthanum zirconate electrolytes obtained by traditional solid-state mixing sintering, lanthanum zirconate ceramic electrolyte sheets obtained by gas-solid sintering consistently exhibit higher ionic conductivity. In terms of density, the lanthanum zirconate ceramic sheets obtained by gas-solid sintering have a density of 97.8%.

[0134] When the holding time was adjusted to 10 hours, and other parameters remained the same as in Example 4, the density of the lanthanum zirconate ceramic sheet obtained by gas-solid sintering was 99.4%. Figure 12 SEM image of lanthanum zirconate electrolyte sheet after gas-solid sintering at 1400℃ for 10 h with 20wt% zinc oxide.

[0135] like Figure 7 The image shows the XRD characterization of the lanthanum zirconate electrolyte sheet after gas-solid sintering in Example 4. The gas-solid sintering temperature was varied, such as... Figure 8 Density and SEM images of lanthanum zirconate electrolyte sheets sintered under gas-solid conditions at different temperatures with the same zinc oxide content were obtained. The density was 92.6% at sintering temperature of 1300℃, 94.7% at sintering temperature of 1350℃, and 97.8% at sintering temperature of 1400℃.

[0136] Change the amount of zinc oxide used, such as Figure 9 Density and SEM images of lanthanum zirconate electrolyte sheets after gas-solid sintering at 1400℃ with different zinc oxide dosages were obtained. The density was 70.2% when the zinc oxide dosage was 0 wt%; 92.7% when the zinc oxide dosage was 5 wt%; 94.0% when the zinc oxide dosage was 10 wt%; 97.8% when the zinc oxide dosage was 20 wt%; and 93.9% when the zinc oxide dosage was 50 wt%.

[0137] Comparative Example 3:

[0138] Lanthanum zirconate electrolyte prepared by conventional solid-state mixing sintering method

[0139] Lanthanum zirconate powder is directly ground and mixed with 5wt% ZnO powder in a mortar. 800mg of the mixed powder is poured into a 20mm diameter mold and pressed into ceramic sheets under 400MPa pressure. The sheets are then sintered in a magnesium oxide crucible at 1400℃ for 5h to obtain lanthanum zirconate electrolyte sheets sintered by the traditional solid-phase mixing method.

[0140] Figure 10 The image shown is a cross-sectional SEM image of the lanthanum zirconate electrolyte obtained by sintering using the conventional solid-state mixing method in Comparative Example 3. The density of the lanthanum zirconate electrolyte obtained by sintering using the conventional solid-state mixing method is 94.3%.

[0141] Figure 11 The comparison shows the ionic conductivity and activation energy of the lanthanum zirconate electrolyte obtained by gas-solid sintering in Example 4 and the lanthanum zirconate electrolyte obtained by conventional solid-phase mixing and sintering in Comparative Example 3. Compared with Comparative Example 3, the lanthanum zirconate ceramic electrolyte sheet obtained by gas-solid sintering in Example 4 consistently exhibits higher ionic conductivity.

[0142] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any form or substance. It should be noted that those skilled in the art can make various improvements and additions without departing from the method of the present invention, and these improvements and additions should also be considered within the scope of protection of the present invention. Any modifications, alterations, and equivalent changes made by those skilled in the art based on the above-disclosed technical content without departing from the spirit and scope of the present invention are equivalent embodiments of the present invention. Furthermore, any modifications, alterations, and evolutions made to the above embodiments based on the essential technology of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A method for preparing ceramics, characterized in that, The preparation method includes the following steps: 1) The precursor powder and polymer solution are ground and mixed, and then pressed into precursor powder cakes; 2) The precursor powder obtained in step 1) is subjected to high-temperature degumming to obtain a porous powder; 3) Place the porous powder cake obtained in step 2) in a crucible covered with oxide, wherein the porous powder cake is placed directly above the oxide and the porous powder cake is not in direct contact with the oxide; heat and cool to room temperature in a sealed environment to obtain the final product. In step 1), the precursor powder is selected from electrolyte precursor powder and electrode precursor powder. The electrolyte precursor powder is lanthanum zirconate powder, and the electrode precursor powder is cobalt tetroxide powder and / or manganese tetroxide powder. In step 3), the oxide is lithium oxide or zinc oxide.

2. The method for preparing ceramics as described in claim 1, characterized in that, It also includes one or more of the following features: B1) In step 1), the mass ratio of the precursor powder to the polymer solution is (85~95):(5~15). B2) In step 1), the polymer solution is a polyvinyl alcohol solution; B3) In step 1), the pressing pressure is 100~400 MPa; B4) In step 1), the pressing time is 1 to 5 minutes; In step 1) of B5), the thickness of the precursor powder is 150~800 μm; In step 2) of B6, the temperature for high-temperature degumming is 700~1200℃; In step 2) of B7), the high-temperature degumming time is 1h~3h; In step 2) of B8, the porous powder cake has a porous structure and a density of 70%~80%; In step 3) of B9), the crucible is a magnesium oxide crucible; In step 3) of B10, the heating temperature is 1050~1800℃; In step 3 of B11, the heating time is 2 to 20 hours.

3. The method for preparing ceramics as described in claim 2, characterized in that, The polymer solution is an aqueous solution of polyvinyl alcohol with a concentration of 5wt% to 15wt%.

4. The method for preparing ceramics as described in claim 1, characterized in that, The lithium oxide is 20 wt% to 50 wt% of the porous powder cake by mass.

5. The method for preparing ceramics as described in claim 1, characterized in that, The zinc oxide is 15 wt% to 30 wt% of the porous powder cake by weight.

6. The application of the ceramic prepared by the method according to any one of claims 1 to 3 in the field of batteries.

Citation Information

Patent Citations

  • Lithium battery cell, lithium battery and preparation method thereof

    CN108365255A

  • All-solid-state composite electrolyte membrane with lithium lanthanum zirconium oxide vertical membrane surface and preparation method of all-solid-state composite electrolyte membrane

    CN115621536A